ANALISIS PERLAKUAN PENYUSUTAN ASET TETAP BERDASARKAN PSAK NOMOR 16 PADA PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA KENCANA KOTA SAMARINDA - Indah Tri Utami Agustini; Sigit Hartoko; Jenglis Lumbanraja (Politeknik Negeri Samarinda, 2021)
The purpose of this research are to find out how the depresiation of Property Plant and Equipment Treatment on Perusahaan Umum Daerah Air Minum Tirta Kencana Samarinda. The research method are using a qulitative, with a descriptive approach, this method are to describe the situation of company systematically about the depresiation treatment of fixced asset, and their compliance with PSAK Number 16. Data obtained through interwiew, observation, documentation, and library studies. The result of this research showed that the depresiation treatment of fixced asset at PERUMDAM Samarinda it is not fully implemented PSAK Number 16, Perusahaan Umum Daerah Air Minum Tirta Kencana Samarinda.the company is downsizing the entire asset group using a stragiht line method, when seen by the regular asset group are dominated by machine, so a straight line methode cannot reflect the asset group’s consumption. The entity has never evaluated the economic age, salvage, the depreciation method used as stated in PSAK Number 16 paragraph 62.